ANALISIS MANAJEMEN WAKTU PADA PEREMPUAN PENGUSAHA PEMPEK RUMAHAN DALAM MEMBANTU MENINGKATKAN PENDAPATAN KELUARGA (STUDI KASUS KOTA PALEMBANG) - Ita (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
The role of women in this globalization era is increasing from time to time. Women are not only required to be just housewives but can also play an active role in improving the family economy. In the end it can help improve family welfare. Increased family welfare can occur due to increased income levels, so that children can get a good level of education, adequate clothing and food, positive education and recreation patterns. Women can play an active role in helping the family economy be interrupted during their free time by arranging good time management. So that the available free time can be used for productive activities and economic value.